Circulating mucosal-associated invariant T cell alterations in adults with recent-onset and long-term oral lichen planus - Xiaoli Wu; Siting Chen; Yinshen Yang; Xiaoheng Xu; Xiaoqin Xiong; Wenxia Meng (BMC Oral Health, 2024)
Abstract Background Mucosal-associated invariant T (MAIT) cells play key roles in many inflammatory diseases. However, their effects on the long-term course of oral lichen planus (OLP) and recent-onset OLP remain unclear. In this study, we aimed to investigate the function of MAIT cells in the different processes of OLP and to explore the immunological background of this disease. Methods The frequency, phenotype, cytokine secretion, and clinical relevance of MAIT cells were investigated. MAIT cells were collected from the peripheral blood of 14 adults with recent-onset OLP (7–120 days after disease onset) and 16 adults with long-term course OLP (>2 years after diagnosis) using flow cytometry and compared with 15 healthy blood donors. Statistical analyses were performed using the GraphPad Prism software. Results MAIT cells from adults with recent-onset OLP exhibited an activated phenotype, as indicated by an increased frequency of CD69+ (p < 0.05) and CD38+MAIT cells (p < 0.01) and elevated production of the proinflammatory cytokine IL-17 A (p < 0.01), compared with healthy adult donors. In adults with long-term OLP, MAIT cells exhibited an activated and exhausted phenotype, characterized by high expression of CD69 (p < 0.01) and PD-1 (p < 0.001) and increased production of granzyme B released (p < 0.01). Compared with recent-onset OLP patients, long-term OLP patients showed a decreased production of CD8+, and CD4−CD8− cells, but an increase in PD-1+ production (p < 0.05). Conclusions Circulating MAIT cells exhibited activation in OLP patients across varying disease durations. Given that PD-1 expression is elevated in adults with long-term OLP, it is reasonable to infer that circulating MAIT cells in long-term OLP may exhibit a more exhausted state than those in recent-onset OLP.